PENGARUH PENAMBAHAN EKSTRAK BUAH NAGA (Hyloceraus polyrhizus) PADA PAKAN BUATAN TERHADAP KECERAHAN WARNA IKAN CUPANG (Betta sp.) - Elmi Patma Insani; salnida yuniarti Lumbessy; Dewi Putri Lestari (Journal of Fish Nutrition, 2021)
The purpose of this study was to analyze the effect of the addition of pumpkin flour (C. moschata D.) and papaya flour (C. papaya) to feed to increase the brightness of the gold fish (C. auratus) color. The method used is an experimental method with a completely randomized design, consisting of four treatments and three replications of P0 0% (Control), P1 10% , P2 20%, P3 30%. Research parameters include carotenoid analysis, hunter’s color test, absolute weight growth, absolute specific growth, absolute length growth , FCR, EPP, survival rate and water quality. The results showed that the addition of a mixture of pumpkin flour and papaya flour in the goldfish can affect the value of feed conversion, feed afficiency, survival rate, carotenoid content and the brightness of the goldfish color on the value of a* (redness), b* (yellowness) and Huebut it does not affect the value of L* (lightness) and the growth of the goldfish